Determination of the Relationship Between the Coronavirus-2019 Phobia Level and Hygiene Behaviors of Nurses - Esra Kılınç Akman; Sevgi Gür; Ayfer Özbaş (Galenos Publishing House, 2023)
Objective:Nurses are in the high-risk group in terms of catching Coronavirus disease-2019 (COVID-19) and infecting their families/relatives and society, as they take part in the diagnosis, treatment and care practices of individuals. Therefore, they are afraid and worried about catching the disease and infecting their families/relatives. During the COVID-19, nurses tried to protect both themselves and their families/relatives from the disease by taking personal protective and general hygiene measures protect themselves and to minimize the transmission routes of the coronavirus. The purpose of this study was to determine the relationship between the COVID-19 phobia level of nurses and their hygiene behaviors.Method:The descriptive and correlation study was carried out with 287 nurses between July-November, 2021. Data were collected using online data collection tools "descriptive information form", COVID-19 phobia (CP19-S)" and "COVID-19 hygiene" scales. Cronbach's alpha values of the scales are respectively; it was found as 0.959 and 0.963.Results:It was determined that the relationships between the total and sub-dimensions of the CP19-S and COVID-19 hygiene scale were examined; correlation coefficients were positive, varying between 0.213 and 0.401, and were found to be weak or moderate in terms of the strength of the relationships.Conclusion:It was determined that when the total score from the CP19-S scale increased, the COVID-19 hygiene scale score also increased. It is recommended that the study be conducted in larger sample groups and that nurses should be taught how to cope with COVID-19 phobia.